Growth through innovation and productivity : the case of South Africa - Ledwaba, Nthabiseng Anne (My University, 2022)
The purpose of this study was to investigate growth through innovation and productivity in the South African economy. The study employed the Autoregressive Distributed Lag (ARDL) approach to analyse the annual time series data from the period 1994 to 2018. The data of the study is quantitative and was collected from the South African Reserve Bank and the World Bank. Due to a decline in investment in innovation in South Africa as compared to Brazil, Russia, India and China, the study recommends increased investment in innovation, which may yield positive results on economic growth given the Fourth Industrial Revolution (4IR) presence. The results of the study indicate that there is a long-run relationship between the variables furthermore, in the short-run research and development (R&D), several patents and manufacturing: Labour productivity has a positive and is statistically significant on GDP. However, labour productivity in the non-agricultural sector is positive but statistically insignificant on GDP. Moreover, the findings, in the long run, reveal that R&D, number of patents, and manufacturing: labour productivity is positive and statistically significant on the economic growth in South Africa while labour productivity in the non-agricultural sector has a negative impact on economic growth. This study recommends that policymakers should aim at increasing government-funded R&D, education and human capital to induce productivity and eventually drive up economic growth in South Africa.
Thesis (M.Com. (Economics)) -- University of Limpopo, 2022
Keywords: Innovation; Labour productivity; South Africa; Research and development; Patent; Autoregressive Distributed Lag; Technological innovations -- South Africa; Labor productivity -- South Africa; Economic development -- South Africa; Industrial productivity -- South Africa; Government productivity -- South Africa